Food for All International Organizations and the Transformation of Agriculture - Lele, Uma (Oxford University Press, 2021)
This book is a historical review of international food and agriculture since the founding of the international organizations following the Second World War, including the World Bank and the Food and Agriculture Organization of the United Nations (FAO), the World Food Programme (WFP) and into the 1970s, when CGIAR was established and the International Fund for Agricultural Development (IFAD) was created to recycle petrodollars. The book concurrently focuses on the structural transformation of developing countries in Asia and Africa, with some making great strides in small farmer development and in achieving structural transformation of their economies. Some have also achieved Sustainable Development Goals (SDGs), particularly SDG2, but most have not. Not only are some countries, particularly in South Asia and sub-Saharan Africa, lagging behind, but they face new challenges of climate change, competition from emerging countries, population pressure, urbanization, environmental decay, dietary transition, and now pandemics. Lagging developing countries need huge investments in human capital, and physical and institutional infrastructure, to take advantage of rapid change in technologies, but the role of international assistance in financial transfers has diminished. The COVID-19 pandemic has not only set many poorer countries back but starkly revealed the weaknesses of past strategies. Transformative changes are needed in developing countries with international cooperation to achieve better outcomes. Will the change in US leadership bring new opportunities for multilateral cooperation?